Lipid profiles are associated with lesion formation over 24 months in interferon-β treated patients following the first demyelinating event. Issue 11 (17th April 2013) - Weinstock-Guttman, Bianca; Zivadinov, Robert; Horakova, Dana; Havrdova, Eva; Qu, Jun; Shyh, Grace; Lakota, Elizabeth; O'Connor, Kerri; Badgett, Darlene; Tamaño-Blanco, Miriam; Tyblova, Michaela; Hussein, Sara; et al.
Abstract : Objectives: To investigate the associations of serum lipid profile with disease progression in high-risk clinically isolated syndromes (CIS) after the first demyelinating event. Methods: High density lipoprotein cholesterol (HDL-C), low density lipoprotein cholesterol (LDL-C) and total cholesterol (TC) were obtained in pretreatment serum from 135 high risk patients with CIS (≥2 brain MRI lesions and ≥2 oligoclonal bands) enrolled in the Observational Study of Early Interferon β-1a Treatment in High Risk Subjects after CIS study (SET study), which prospectively evaluated the effect of intramuscular interferon β-1a treatment following the first demyelinating event. Thyroid stimulating hormone, free thyroxine, 25-hydroxy vitamin D3, active smoking status and body mass index were also obtained. Clinical and MRI assessments were obtained within 4 months of the initial demyelinating event and at 6, 12 and 24 months. Results: The time to first relapse and number of relapses were not associated with any of the lipid profile variables. Higher LDL-C (p=0.006) and TC (p=0.001) levels were associated with increased cumulative number of new T2 lesions over 2 years. Higher free thyroxine levels were associated with lower cumulative number of contrast-enhancing lesions (p=0.008). Higher TC was associated as a trend with lower baseline whole brain volume (p=0.020). Higher high density lipoprotein was associated with higher deseasonalised 1, 25-dihydroxy vitamin D3 (p=0.003) levels and a trend was found for deseasonalised 25-hydroxy vitamin D3 (p=0.014). Conclusions: In early multiple sclerosis, lipid profile variables particularly LDL-C and TC levels are associated with inflammatory MRI activity measures.